2015
DOI: 10.1179/2047773215y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

WHO Dengue Case Classification 2009 and its usefulness in practice: an expert consensus in the Americas

Abstract: Introduction: In 2009, the new World Health Organization (WHO) dengue case classification -dengue/ severe dengue (D/SD) -was introduced, replacing the 1997 WHO dengue case classification: dengue fever/dengue haemorrhagic fever/dengue shock syndrome (DF/DHF/DSS). Methods: A 2-day expert consensus meeting in La Habana/Cuba aimed to (1) share the experiences from Pan American Health Organization (PAHO) member states when applying D/SD, (2) present national and local data using D/SD, and (3) agree with the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 20 publications
1
37
0
1
Order By: Relevance
“…The clinical spectrum of DENV is wide and varies from asymptomatic infection to an acute flu-like illness with or without warning signs of shock. 1 Approximately half of infections are asymptomatic even though these individuals have a sufficiently high enough viral load to transmit virus back to the mosquito population. 2 Symptomatic infection generally leads to high fever, headache, retroorbital pain, myalgias, arthralgias, and a diffuse erythematous maculopapular rash.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical spectrum of DENV is wide and varies from asymptomatic infection to an acute flu-like illness with or without warning signs of shock. 1 Approximately half of infections are asymptomatic even though these individuals have a sufficiently high enough viral load to transmit virus back to the mosquito population. 2 Symptomatic infection generally leads to high fever, headache, retroorbital pain, myalgias, arthralgias, and a diffuse erythematous maculopapular rash.…”
mentioning
confidence: 99%
“…3 Hemorrhage may also be evident in the form of petechiae, skin bruising, or subconjunctival hemorrhage. 1,3 Severe dengue with shock is the most serious manifestation of DENV infection, and it can be life threatening. 1 Warning signs include abdominal pain, abdominal tenderness, persistent vomiting, ascites, pleural effusion, mucosal bleeding, lethargy, restlessness, hepatomegaly, increase in hematocrit and a rapid decrease in platelet count.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, that used WHO case definition of DEN as the standard and evaluated the same RDT that we have evaluated the sensitivity and specificity was reported very low, probably because of using the clinical criteria as reference marker, that itself is debatable . Moreover, it is reported that the RDTs have different sensitivity and specificity in primary and secondary infection, Timing and storage of specimen, and to the infection by different serotypes .…”
Section: Discussionmentioning
confidence: 89%
“…However, the majority of experts attending a consensus meeting in Latin America felt that the 2009 WHO classification is helpful in identifying cases of dengue correctly for pathophysiological research, although they also recommended ongoing research to improve the sensitivity and specificity of the definitions. [32].…”
Section: Discussionmentioning
confidence: 99%